Perencanaan Rute Evakuasi pada Kasus Kebocoran Pipa Gas Alam dengan Simulasi Berbasis Computational Fluid Dynamic - Adhi Setiawan; Tri Bagus Setiawan; Agung Nugroho; Muhammad Luqman Ashari (JST (Jurnal Sains Terapan), 2018)
Melting of metals generally used the energy source of natural gas which is flowed through a pipeline at high pressure. Production activities in companies that use these gases have high potential hazards because they can cause fires or explosions if not managed properly. This study aims to analyzed natural gas dispersion in the event of gas pipeline leak, determine assembly point and evacuation route map plan for workers in the event of emergency condition. Natural gas dispersion was simulated using Computational Fluid Dynamic Ansys Fluent. Results of simulation showed distribution concentration of natural gas indoors at leakage almost uniform with concentration between 5%-13,17%. At that concentration the mixture of air and natural gas has the potential to explode because it is in the range of natural gas flammability. The maximum natural gas concentration of 13.17% at a height of 12 m above the leak hole. Generated two points Assembly point based on the calculation of blast radius with total area of 58,500 cm2 and can accommodate as many as 65 workers.Keywords :CFD Simulation, Natural Gas Dispersion, Assembly point, Evacuation Rute